2011
DOI: 10.1353/csd.2011.0004
|View full text |Cite
|
Sign up to set email alerts
|

Student-Generated Protective Behaviors to Avert Severe Harm Due to High-Risk Alcohol Consumption

Abstract: High-risk alcohol consumption is a significant problem on college campuses that many students see as a rite of passage in their development into adulthood. Developing effective prevention campaigns designed to lessen or avert the risks associated with alcohol consumption entails understanding how students perceive harmful consequences as well as the ways they protect themselves while drinking. This study used survey research to determine what undergraduate students perceived to be the most severe alcohol-relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 27 publications
1
2
0
Order By: Relevance
“…Although the majority of these experiences involve alcohol, alcohol interventions alone are not sufficient for reducing related problems as they often include components of social interaction or environmental risk. Consistent with previous work (Smith et al, 2011), our findings show college students already endorse a wide variety of CPBs. Within the current study, eight out of 13 strategies were endorsed as being used regularly by more than half of the sample.…”
Section: Discussionsupporting
confidence: 92%
“…Although the majority of these experiences involve alcohol, alcohol interventions alone are not sufficient for reducing related problems as they often include components of social interaction or environmental risk. Consistent with previous work (Smith et al, 2011), our findings show college students already endorse a wide variety of CPBs. Within the current study, eight out of 13 strategies were endorsed as being used regularly by more than half of the sample.…”
Section: Discussionsupporting
confidence: 92%
“…According to Arnett (2005), emerging adulthood is a period during which numerous developmental changes (such as changes in residence, employment, education, and romantic relationships) occur and therefore is defined as the transitional period from high school to young adulthood. Many who are in emerging adulthood see excessive alcohol consumption to be a part of a rite of passage (Smith et al , 2011). Boys et al (2003) reported that in the UK a normalization of involvement with alcohol occurred between the ages of 15 and 17; despite still being under the legal drinking age of 18, most 17‐year‐olds were socialised into adult patterns of drinking behaviour, which, for a substantial minority, included consumption above recommended levels, drunkenness, and negative consequences.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The university student years are a time when many young adults engage in the negotiation, development, and management of orientations to sex and sexuality. Previous research has examined sex-related phenomena including sex as a characteristic of risky behavior (see, e.g., Lindgren et al, 2009;Smith et al, 2011), the practice of casual sex (see, e.g., Grello et al, 2006;Paul and Hayes, 2002) and sexual relationships between students and academic staff (see, e.g., Richards et al, 2014;Taylor, 2011). However, less is known about how students discuss and negotiate matters of sexual behavior in naturally occurring interactions, particularly in online communities.…”
Section: Introductionmentioning
confidence: 99%